Pengaruh pertumbuhan aset, risiko bisnis, dan struktur modal terhadap profitabilitas perusahaan ritel yang terdaftar pada BEI periode 2017-2021 - Zulfikar, Rayhan Hardian; Suherman, Suherman; Mahfirah, Titis Fatarina (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
This research aims to investigate the influence of asset growth, business risk, and capital structure on the profitability of retail companies listed on the Indonesia Stock Exchange (IDX) during the period 2017-2021. The study involves three variables: independent variables (asset growth, business risk, and capital structure), dependent variable (profitability), and control variables (liquidity, firm size, and activity ratio). The sampling method employed is purposive sampling. Data collection techniques involve accessing financial reports from the Indonesia Stock Exchange (IDX) website and the official websites of the companies. The analytical technique used is the panel data regression method. The partial results of this research indicate that asset growth does not significantly affect ROA, ROI, and ROE, while it significantly influences ROS positively. Business risk does not affect ROA, ROI, and ROS, whereas business risk significantly affects ROE positively. Capital structure does not affect ROA, ROE, and ROI, while it significantly influences ROS negatively. It can be concluded that increasing asset growth can affect the company's profitability.